Service provision of non-invasive prenatal testing for Down syndrome in public and private healthcare sectors: a qualitative study with obstetric providers - Olivia Miu Yung Ngan; Huso Yi; Shenaz Ahmed (BMC, 2018)
Abstract Background Cell-free fetal DNA sequencing based non-invasive prenatal testing (NIPT) for Down syndrome (DS) has become widely available. In Hong Kong, obstetric providers in the public sector refer women identified at high risk of having a child with Down syndrome to obstetric providers in the private sector for NIPT. Little is known about how the NIPT has been adopted in the public sector where DS screening is provided for free of charge. The study aimed to identify the factors influencing providers' role enactment, such as consultation and referral, in the service provision of NIPT for DS in public and private healthcare sectors. Methods In-depth interviews were conducted with 20 obstetric providers offering NIPT in Hong Kong. Thematic narrative analysis was used to identify (i) the factors considered by participants when referring women for NIPT for Down syndrome in public and private healthcare sectors and (ii) their perceptions of the need to integrate NIPT into the current public antenatal service. Results Participants raised concerns about the lack of transparent referral guideline between public and private sectors for NIPT. Public obstetric providers reported little obligation to provide women with much information about risks and benefits of NIPT as it was not provided by public sectors. Some private providers assumed that women referred from the public sector had already received sufficient information about NIPT. The providers were also concerned about potential application of NIPT for further detection without regulation. Conclusions Although the providers had good knowledge of clinical advantages of NIPT over conventional screening, they were uncertain about how to introduce NIPT to women. Guidelines are necessary to enable better coordination of public and private sectors services to enable women to make informed choices about the uptake of NIPT.